Fenomena Calon Tunggal dan Arah Gerak Partai Politik Pada Pemilihan Kepala Daerah Kabupaten/Kota 2024 - Fernando Holqi, Fikri Gali; Handayani, Febta Fina; Astuti, Widya Puji; Permatasari, Putri Diah; Rahman Putra, Rizki Ananda (Universitas Indo Global Mandiri, 2025)
The purpose of this article is to analyze the phenomenon of single candidates and the direction of motion of political parties supporting and supporting single candidates in the 2024 Regency / City Regional Head Elections after the Constitutional Court Decision Number 60/PUU-XXII/2024. This research was conducted by qualitative method with new institutionalism approach specifically rational choice institutionalism. The data collected consists of secondary data, namely KPU data processing, journals, and books. Data analysis techniques include data collection and descriptive interpretation. Theoretical analysis include power elite theory by Wright Mills. The results of the study state that the Constitutional Court Decision No. 60 / PUU-XXII / 2024 provides an opportunity for each political party to carry regional head candidates referring to the Constitutional Court's indicators, but after the decision, there are still findings of single candidates. This single candidate is caused by the buildup of a coalition of political parties, dominated by “the top leaders” or the upper class with “polical” specifications which basically have resources, the tendency of political parties to form coalitions with the winning party of the previous Pilkada or electoral-based so as to increase the potential to win political contestation. The elite group or “the top leaders” carry out dualism of roles, namely elite actors behind the scenes or as local leaders of political parties and in front of the public space or running for public office.